Manajemen Santri Baru sebagai Sistem Preventif dalam Mitigasi Bullying di Pesantren - Munawwaroh; Firdausi Nur Harini; Munib; Ismatul Maula Ramadhani (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
This study examines how the management of new students functions as a preventive system in mitigating bullying behavior in Islamic boarding schools. Until now, research on bullying in pesantren has mostly focused on case handling and counseling approaches, while the role of student management during the initial admission and adaptation phase as a structural prevention instrument is still relatively limited. This study uses a qualitative approach with a case study design conducted at Pondok Pesantren Tanwirul Ulum Umbulsari Semboro Jember through participant observation, in-depth interviews, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with validation through triangulation and member checking. The research results show that bullying mitigation is implemented through three integrated stages of new student management, namely: (1) acceptance and orientation that combines administrative, adaptive, and cultural mechanisms; (2) adaptation guidance and ongoing character development; and (3) internal supervision and regulation through restorative justice-based counseling, involvement of students' guardians, and formal behavior agreements. These three stages form a preventive system that not only addresses cases of bullying but also suppresses its structural and cultural roots. This study contributes to the development of Islamic education management by positioning new student management as a preventive governance framework in bullying mitigation in pesantren.